Communicative Teaching for Elementary Students with “Like and Dislike” Minigame - Adrimurlan, Raditya Daffa; Iskandar, Farhan Alfarizi; Mahendro, Rasika Tasdyatta; Bawarti, Era; Hadiyansyah, Dhuha; Herwandar, Ria (UniversitasAl Azhar Indonesia, 2023)
The activities of the National Movement for Mental Revolution (GNRM) are located at Al Fityan School Tangerang. These activities aim to introduce teaching and learning by using CLT or the Communicative Language Teaching method through mini-games. The main problem is that elementary students require more fun in teaching due to their changing moods and mental states to absorb experiences and knowledge. We handled the 4th-grade elementary school students, all of them were boys. The teaching was focused on various topics, however, this paper was focused on “like and dislike”, knowing that children tend to express their moods and feelings. This activity was based on 28 samples based on questionnaires collected from students. The findings show that students were able to express themselves when mentioning two things (what do they like and what don’t they like) with proper vocabulary and grammarKeywords: Elementary School, Qualitative, CLT, Like, and Dislike